2018
DOI: 10.1093/ajcp/aqy122
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly High Prevalence of Cystoisospora belli Infection in Acalculous Gallbladders of Immunocompetent Patients

Abstract: ObjectivesIndications for cholecystectomy have changed dramatically over the past three decades. Cystoisospora belli has been reported in cholecystectomy specimens of immunocompetent patients. The present study was designed to determine the prevalence and clinical association of C belli in the gallbladder.MethodsThe study included retrospective review of cholecystectomy specimens (n = 401) removed for various indications, and a prospective cohort of cholecystectomy specimens (n = 22) entirely submitted for his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…After a review of these reports, it became clear that details regarding C. belli developmental stages were lacking. Additionally, non-protozoal structures in the gallbladder of patients that were initially identified as C. belli (Lai et al ., 2016; Martelli and Lee, 2016; Akateh et al ., 2018; Noor et al ., 2019) are now considered artefacts. Therefore, an intensive search was made to identify the developmental stages of C. belli in the duodenum and common bile duct of two patients reported previously (Walther and Topazian, 2009; Swanson et al ., 2018).…”
Section: Morphology and Life Cyclementioning
confidence: 99%
“…After a review of these reports, it became clear that details regarding C. belli developmental stages were lacking. Additionally, non-protozoal structures in the gallbladder of patients that were initially identified as C. belli (Lai et al ., 2016; Martelli and Lee, 2016; Akateh et al ., 2018; Noor et al ., 2019) are now considered artefacts. Therefore, an intensive search was made to identify the developmental stages of C. belli in the duodenum and common bile duct of two patients reported previously (Walther and Topazian, 2009; Swanson et al ., 2018).…”
Section: Morphology and Life Cyclementioning
confidence: 99%
“…have been detected in primates in Ghana, but their role in transmission remains uncertain [ 15 ]. After infection, the parasites can be found in the epithelium of the intestines, the bile duct and the gallbladder [ 1 , 16 , 17 ]. In particular for the latter location, however, histological misidentifications have been reported as well [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the gallbladder, they are characteristically associated with epithelial injury or inflammation, lack of distinct vacuoles, and show negative staining by Alcian blue. 17 Thanatosomes have mostly a membrane-bound ultrastructure in contrast to the non-membrane bound fibrillary aggregates seen in inclusions. 27 Some groups have also suggested the possibility of abortive infection by a related animal species of the organism.…”
Section: True Cystoisospora Versus Inclusions: Compare and Contrastmentioning
confidence: 99%
“…This was followed by multiple publications, abstract presentations at USCAP (United States and Canadian Academy of Pathology), and Twitter feeds including studies on pediatric cholecystectomies. 11-17 The majority of the studies reported an increased incidence of these organisms in acalculous cholecystectomies. Among acalculous cholecystectomies, no increased occurrence was noted in biliary dyskinesia.…”
Section: Beginning Of the Pseudo-cystoisospora Epidemicmentioning
confidence: 99%
See 1 more Smart Citation